PENGEMBANGAN LAYANAN PERPUSTAKAAN SEKOLAH MENGGUNAKAN APLIKASI VISUAL BASIC 2010 DI SMP N 1 BATANG ANAI - Neldawati Neldawati; Alwen Bentri (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
This study aims to develop school library service as a support for the performance library staff or librarians in SMP N 1 Batang Anai. This type of research is research and development (Researt and Development / R & D). The development research model is a procedural model with research subjects 4 respondents, consisting of 2 media expert validators and 2 library experts namely SMA N 1 Batang Anai. The research sample was 4 library officers at SMP N 1 Batang Anai middle School. The results of the validity test from the media and library aspects show that the application program is valid with mild revisions and from the employee / librarian point of view it is very practical to use. Thus it can be concluded that the product / program for developing school library services using Visual Basic 2010 applications is feasible to use improving the quality and effectivenessof library services.  Keywords: Application library service program visual basic 2010